The study of ontogenesis of Centaurea bipinnatifida (Trautv.) Tzvel. in the condition of the city of Karaganda - Asanova, G.K.; Dodonova А.Sh.; Ishmuratova М.Yu.; Push, W. (Fundamental and Experimental Biology, 2020)
The results of the study of the ontogenesis of Centaurea bipinnatifidain the conditions of introduction of the city of Karaganda are presented in the article. The introduction into the culture of this species is due to the need for its preservation and reproduction in order to obtain biologically active substances. Four age periods (latent, virgin, generative and senile) and nine age states (seedlings, juvenile, immature, adult vegetative, young generative, middle age generative, old generative, sub-senile and senile) have been identified. Morphological features of each period and state, degree of development of above-ground and underground organs are determined. The duration of the small cycle of ontogenesis in the culture of Centaurea bipinnatifida was 3–4 years, in nature — 6–8 years. There has been an excess of crop plants over wild-growing individuals in size. The ontogenesis phases in culture are faster than under natural conditions.